A experiência de depressão na contemporaneidade: uma compreensão fenomenológico-existencial - Barbosa, Synara Layana Rocha (2012)
The depression is one of the most common forms of getting ill nowaday. Due to the increase in incidence of depression cases registered worldwide, this theme has been the subject of important studies, especially regarding the symptomatological description and biological etiology of the disease. This research had the objective to understand the unique experience of depression experienced by people who recognize themselves in depression, under the focus of existential phenomenology of Martin Heidegger. To reach the proposed objective, individuals narratives interviews were conducted with four participants, starting from the triggering question, "from your experience, how is for you to being depressed?". The survey revealed that depression affects the whole person and is related to stressful life contexts. Depression was narrated as an experience of disempowerment and lack of self esteem and personal worth. The collaborators of the research referred to the depression from sad, angry, bored and pessimistic mood. The time is experienced as a restriction to the projective opening towards the possibilities of being in which the future is seen as catastrophic and the past lived as debt and guilt. The corporeality, in depression is experienced through the weight, fatigue and pains for no reason. The space is lived from the notion of fall and collapse. We also realized the desire for isolation and avoidance of social contact. Suicide is desired and represents the end of the suffering in life. The depression has proved, still, very stigmatized, because it is discredited and misunderstood. The stigma also addressed to the experience of hospitalization and the unsuitability to the socially imposed standards of beauty, which generates enough suffering to the depressed person. The medication was described based on its positive effects, as a balance and suffering reducer, but also as a producer of dependence. Were also identified according to the collaborators, traces of selfdemand, ordenality and being-for-others, characteristic of typus melancholicus. This study contributes to an understanding of the depression that goes beyond the merely biological perspective and symptomatology of the pathology. The investigation of the depressive experience, through the lens of Heidegger's phenomenology, showed us the phenomenon of the depression in their singularity, complexity and multiple meanings, showing the close relationship between the formation of the depression and the context of personal and social life of the participants